On the Stability of Non‐fullerene Acceptors and Their Corresponding Organic Solar Cells: Influence of Side Chains. (11th August 2022) - Zhou, Bojun; Wang, Liang; Liu, Yang; Guo, Chuanhang; Li, Donghui; Cai, Jinlong; Fu, Yiwei; Chen, Chen; Liu, Dan; Zhou, Yinhua; Li, Wei; Wang, Tao
Abstract: Side chain engineering is a widely explored strategy in the molecular design for non‐fullerene acceptors (NFAs). Although the relationship between side chain structures and optoelectronic properties of NFAs is well clarified, the effect of side chain structures on the stability of NFAs and their corresponding organic solar cells (OSCs) is rarely reported. Herein, a series of Y‐family NFAs with varying side‐chains are studied to investigate their degradation upon multiple stresses including water, oxygen from ambient, chemical environment from ZnO electron transport layer, temperature, and ultraviolet light. The results show that all of these Y‐family NFAs are highly stable against water and oxygen in ambient dark condition, while their photochemical and thermal stabilities decrease with the increasing side chain length. NFAs with shorter side chains are not only more resistant to photo‐oxidation and photocatalytic reactions, but also can hamper the formation of large phase‐separated NFA domains upon storage in both glovebox and ambient conditions. As such, the PM6:NFA OSC with short side‐chain NFA also exhibits superior operational stability, associating with a higher T 80 lifetime. This study demonstrates that the side chains must be considered to obtain stable OSCs. Abstract : The Y‐family non‐fullerene acceptors (NFAs) with shorter side chains are found not only more resistant to photo‐oxidation and photocatalytic reactions, but also can hamper the formation of large phase‐separated NFA domains upon storage in both glovebox and ambient conditions, resulting in superior operational stability.